2019
DOI: 10.3390/ijerph16050733
|View full text |Cite
|
Sign up to set email alerts
|

Combined Assessment of Preschool Childrens’ Exposure to Substances in Household Products

Abstract: Understanding how indoor-air contaminants affect human health is of critical importance in our developed society. We assessed the combined exposure by inhalation of preschool children and children to household products. A total of 1175 families with 72 infants, 158 toddlers, 230 children, and 239 youths were surveyed to determine the combined respiratory exposure concentrations and amounts associated with 21 substances in eight household product groups. We determined the mean concentrations of these substances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This is very important to keep children away from having direct and indirect contacts with the hazardous materials at homes. Infants and toddlers are unintentionally more exposed to these household products by inhalation, due to relatively longer periods of time spent indoors in homes than adults [14,17]. The study also revealed that open burning was the most reported and preferred method of disposal of household hazardous materials.…”
Section: Household Hazardous Materials Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is very important to keep children away from having direct and indirect contacts with the hazardous materials at homes. Infants and toddlers are unintentionally more exposed to these household products by inhalation, due to relatively longer periods of time spent indoors in homes than adults [14,17]. The study also revealed that open burning was the most reported and preferred method of disposal of household hazardous materials.…”
Section: Household Hazardous Materials Management Practicesmentioning
confidence: 99%
“…The indiscriminate use of household products and exposure to specific substances has been linked to the development of respiratory hypersensitivity or asthmatic symptoms in some susceptible individuals. Also, due to their comparatively longer time spent indoors in homes than adults, infants and toddlers are unintentionally exposed to these substances by inhalation [14].…”
Section: Introductionmentioning
confidence: 99%